INSTITUTIONAL ISSUES FOR THE BULGARIAN TOURISM INDUSTRY FOLLOWING AMENDMENTS IN TAX LEGISLATION - M. Georgiev; Iv. Dimitrova (Trakia Journal of Sciences)
The current study examines the institutional issues in the tourism sector of Bulgaria in terms of the impact of the by-law Ordinance № 18 of 13 December 2006 on the registration and reporting of sales in retail outlets through fiscal devices. The research applies: (1) defining the legal “error”; (2) the information asymmetries that pose a problem to the coordination mechanisms of the organization are described; (3) the negative economic effects are presented through the measurement of transaction costs. In conclusion, proposals have been made to improve this section of the institutional environment.